Art Music by Caribbean Composers: Bonaire - Gangelhoff, Christine; LeGrand, Cathleen (International Journal of Bahamian Studies, 2013)
Bonaire has musical traditions similar to those of its Antillean neighbors, Aruba and Curacao. All three islands “share a neo-African, drum-centred tradition known as tambu (in Bonaire often referred to as bari), a quintessential Netherlands Antilles folk music” (Bilby, 2013, para. 4). Tumba, a unique mixture of tambu music with other, more modern musical elements, is a particularly popular local musical style (Bilby, 2012).